Prospective study of structural and biomechanical factors associated with the development of plantar fasciitis in female runners - Davis, I. S.; Milner, C. E.; Hamill, J. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland, 2004)
Plantar fasciitis is one of the 5 most common injuries that runners sustain (vanMechelen, 1992). It is believed that this injury is a result of repetitive strain to the plantar fascia. Warren at al. (1987) reported that runners, either currently or formerly experiencing PF, exhibited greater pronation of the foot while in a loaded stance position than runners with no history of this injury. Results of these preliminary, prospective data suggest that there may be predisposing structural and mechanical factors to the development of plantar fasciitis. These results may be strengthened as additional subjects are added. With additional subjects, regression analyses, utilizing both structural and mechanical variables will be performed. It is hoped that, as this research progresses, we will gain further insight into the cause of plantar fasciitis in runners. This will help us to develop optimal treatment interventions for this common injury.